Hypertension and associated risk factors in some selected rural areas of Bangladesh - Ahmed, Alauddin; Rahman, Mosiur; Hasan, Rabiul; Shima, Salma Akter; Faruquee, M. H.; Islam, Tariqul; Haque, Syed Emdadul (International Journal of Research in Medical Sciences, 2017)
Background:Although, Bangladesh has the ninth highest rate of age-standardized rates of deaths due to chronic diseases, mostly due to cardiovascular diseases and diabetes. There is scanty literature on the estimated burden, and the determinants of hypertension in the rural areas of Bangladesh. Methods:This facility based cross-sectional survey was conducted at sub-urban field research clinic from four unions of Araihazar upazilla of Narayangong district, Bangladesh. The analyses were based on 212 male and female respondents of more than 30 years of age. The prevalence of hypertension was the main outcome of interest. Results:The study found that the prevalence of systolic hypertension among the respondents is 15.6% and that of diastolic pressure is 12.3%. Systolic pressure was found in an increasing manner with the increase of age and BMI. Tendency of increase systolic pressure was observed among those who took extra salt. Significant association was also found between increasing systolic pressure with the heart disease. No significant association was found between increasing systolic pressure with smoking habit, physical activity and vegetable intake and with the development of systemic diseases namely cardiovascular disease (CVD), diabetes mellitus and coronary obstetrics pulmonary disease. Conclusion:Suggestion on regular periodical health check-up especially including blood pressure monitoring and restriction of taking extra salt to all the people of age more than 30 years is recommended.